Vulnerability assessment of ports and industrial clusters against catastrophes - Cao, Xinhu (2018)
Catastrophes, with the features of high negative impact and low frequency, are causing increasing losses to the human society due to the increasing exposure and vulnerability. Seaports are critical lifeline infrastructures in coastal cities and are at the same time vulnerable to both natural and man-made catastrophes, such as typhoon, earthquake, fire, and explosion. Any disruptions to a seaport will have a direct impact on the supply chain where the port lies and have a second order or even a third order propagation to the industrial clusters in the hinterland. A literature review reveals a research gap on port multi-dimensional vulnerability assessment against catastrophes, which includes assessments of physical, functional, institutional, economic and interdependency aspects of port vulnerability. Therefore, to fill the gap, this study firstly identifies the major port catastrophic hazards by literature review. Based on the framework, port vulnerability is assessed against non-repetitive catastrophes by utilizing the method of vulnerability index which integrates the fuzzy evidential reasoning (ER) and the fuzzy technique for order preference by similarity ideal solution (TOPSIS). By using Tianjin Port Explosion in 2015 as the case study, vulnerability estimates of the four port sub-systems as well as the whole port system in two assessment periods are obtained. It is found that the storage system is the most vulnerable subsystem after the explosion, while the vulnerability condition of the loading and unloading system improves the most after the first round of port recovery. Further, port vulnerability assessment against repetitive catastrophes is conducted by using the developed port operation simulation-based model. The relationship between catastrophe magnitude and port loss is revealed by quantifying decreased port throughput and physical damages. The typhoon hazard and the Port of Shenzhen, China is selected as the case study. It is estimated that a worst-case scenario typhoon attack could cause a total loss of 0.91 USD billion in the studied terminal, which is approximately three times the terminal net profit in 2015. Finally, the research takes a further step in considering the hinterland industrial clusters into the research scope. VIII Propagation of port vulnerability to hinterland industrial clusters is evaluated by an original three-layer port-cargo-industrial cluster model. The key seaports and industrial clusters in Guangdong province, China as well as the typhoon hazard are used as examples. It is identified that the most vulnerable industrial cluster of Guangdong is the petrochemical industrial cluster when facing typhoon-induced port disruptions in the import mode, while the textile and apparel industrial cluster is the most vulnerable one in the export mode. Consequently, the port and industrial clusters vulnerability estimates obtained from this study could be used by decision makers in identifying and prioritizing critical port protection targets, ship route planning, and risk mitigation strategy formulating.